THE USE OF DICTOGLOSS ON STUDENTS’ LISTENING COMPREHENSION - Handayani, Cici (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The aim of the study was to figure out whether the use of dictogloss has a significant effect on the students’ listening comprehension on the second semester students of Polytechnic Unggul LP3M Medan (AKAP2A/2023). The method of this study was classroom action research which had three cycles whereby there were two meetings for each cycle. Each cycle consisted of four steps: planning, implementing, observation and reflection. The field notes and test constituted the research data. The data were analyzed through assembling the data, coding, comparing, building interpretations, and reporting the outcomes. The research findings showed that Dictogloss could improve: (1) the students’ ability in listening comprehension; (2) the students’ vocabulary; (3) the students’ ability answering Short Conversation questions correctly